Exploring the impact of mobile and migrant populations on mass drug administration coverage and effectiveness in Africa: A scoping review protocol - Moussa Sangare; Yaya Ibrahim Coulibaly; Prithi Ravichandran; Abdoul Fatao Diabate; Claudia Duguay; Carol Vlassoff; Manisha A. Kulkarni; Alison Krentel (PLoS ONE, 2025)
Background Neglected tropical diseases (NTDs) affect populations in tropical regions, particularly low- and middle-income countries with limited economic and health resources. Mass drug administration (MDA) is a strategy for controlling and eliminating NTDs by treating entire at-risk populations to reduce parasite loads, interrupt transmission, and prevent reinfection. It is cost-effective, and promotes equity by reaching underserved communities. MDA is a critical approach to controlling and eliminating NTDs. Mobile populations in Africa such as nomadic groups and internally displaced persons, may lack access to MDA, which poses challenges to NTD elimination. This study aims to explore the influence of population mobility on the implementation, effectiveness, and sustainability of MDA in Africa. Materials and methods This scoping review adheres to the PRISMA extension for scoping reviews and Joanna Briggs Institute (JBI) methodology. PCC (Population, Concept, Context) serves as the foundation for the study. Relevant papers published after 2000 will be identified through a comprehensive search of Medline Ovid, Embase, Web of Science, and gray literature. Studies addressing challenges to MDA in Africa’s and related to mobile populations will be included. An Excel spreadsheet modified from the JBI will be used for data extraction and analysis. Conclusion The results of this review will shed light on how MDA coverage is affected by the phenomenon of mobile and migrant populations and what effective approaches, if any, have been used to address this problem and improve overall population access to MDA.